2005
DOI: 10.1007/s10750-005-4369-x
|View full text |Cite
|
Sign up to set email alerts
|

Iron–sulphur–phosphorus Interactions: Implications for Sediment Buffering Capacity in a Mediterranean Eutrophic Lagoon (Sacca di Goro, Italy)

Abstract: The interactions among sedimentary cycles of sulphur, iron and phosphorus were investigated in the eutrophic Sacca di Goro lagoon (Northern Adriatic coast, Italy) in order to assess the iron buffering capacity of the sediment. Three stations were chosen, which represented different primary producer communities, hydrodynamics and sediment characteristics. Station G was close to the outlet of the Po di Volano river, station 4 was in the central part of the lagoon under tidal influence and station 17, in the shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 46 publications
(61 reference statements)
1
55
0
Order By: Relevance
“…Fe is perhaps the most versatile element, and the redox cycling of Fe exerts a wide influence on the biogeochemical cycling of N, S, and P in sediment environments (Azzoni et al 2005;Weber et al 2006;Wilms et al 2007). Pore water and sediment profiles of Fe geochemistry also showed active Fe(III) reduction at depth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fe is perhaps the most versatile element, and the redox cycling of Fe exerts a wide influence on the biogeochemical cycling of N, S, and P in sediment environments (Azzoni et al 2005;Weber et al 2006;Wilms et al 2007). Pore water and sediment profiles of Fe geochemistry also showed active Fe(III) reduction at depth.…”
Section: Discussionmentioning
confidence: 99%
“…immediately, and the second subsample was acidified with 1 mL of 0.5 mol/L HCl to prevent precipitation of Fe (Azzoni et al 2005) and was then measured for Fe(II) in triplicate using the 2,2,-bipyridyl assay (Moss and Mellon 1942). Total organic carbon (TOC) of sediment was measured using an Elementar Vario TOC system (China).…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of Fe(II) in the porewaters at depths >35 mm is the result of sulfate reduction which subsequently causes the precipitation of iron-sulfides 46,47 . Dissolved Mn continued to increase, peaking at 60 mm depth, which was also the depth at which the Fe(II) decreased to concentrations similar to those at the SWI.…”
Section: Silver Iron and Manganese Chemistry In Freshwater Sedimentmentioning
confidence: 99%
“…In addition, recent field and laboratory experiments have shown that under anoxic conditions, the build-up of sulphide by the bacterial sulphate reduction induces enhanced release of phosphate from coastal lagoon sediments. The interactions of sedimentary iron and sulphur cycles have implications for phosphorus cycling and its availability to macroalgae (HEIJS et al, 2000;AZZONI et al, 2005). Evidence to show that the sulphide metabolism is critical for the release of non-iron-bound phosphate (organic and/or Ca-bound phosphate) was also obtained however, the responsible mechanism has not yet been elucidated (HEIJS et al, 2000).…”
mentioning
confidence: 99%